Improving Students’ Participation In English Learning Through Flashcards: A Classroom Action Research At Mi Nurul Mun’im - Nurfitriani Nurfitriani; Bradhiansyah Tri Suryanto; Siti Umniatul Khoiriyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Low student participation, with only 51% of 33 students actively involved, was a primary challenge in English learning for Class 3B at MI Nurul Mun'im. This Classroom Action Research (CAR) aimed to enhance student participation through the implementation of interactive flashcards. The study adopted the Kemmis and McTaggart model, conducted over two cycles, each comprising planning, acting, observing, and reflecting. Cycle I focused on using basic flashcards for guessing games and reading aloud activities with the theme